Smart globalization : the Canadian business and economic history experience - Anastakis, Dimitry, 1970-; Smith, Andrew, 1976- (University of Toronto Press, 2014)
Inspired by the work of economists Ha-Joon Chang and Dani Rodrik, editors Andrew Smith and Dimitry Anastakis bring together essays from both historians and economists in this collection to test claims that wealth comes from either protectionism or free trade.